Social and Cultural activities and lobbyism - V. A. Saprykin (Проблемы постсоветского пространства, 2017)
The article discusses the construction of public relations as a cultural construction. Analyzed this form of social and cultural activities as lobbying. Presented by the understand- ing of the modern lobbying in Russia.